Stiffened steel box columns. Part 2 Ductility evaluation. - Usami, Tsutomu (Earthquake engineering & structural dynamics.)
The purpose of this study is to evaluate the ultimate strength and ductility capacity of stiffened steel box columns failed by local and overall interaction instability under a constant compressive axial force and cyclic lateral loading. In a companion paper, a finite element formulation accounting for both geometrical and material non-linearity was developed to obtain cyclic hysteretic behaviour of such columns. In this paper, the effect of loading patterns on the cyclic inelastic behaviour is first studied; then, a parametric study is carried out to investigate the effects of flange plate width thickness ratio parameter, column slenderness ratio parameter, stiffener's equivalent slenderness ratio parameter, magnitude of axial load, and material type of stiffeners on the strength and ductility of the columns. Last but not least, empirical formulae of both the ultimate strength and ductility capacities are proposed for stiffened steel box columns, and the limit values of various parameters for the required ductility demand are also discussed.